1960
DOI: 10.1111/j.1744-7348.1960.tb03510.x
|View full text |Cite
|
Sign up to set email alerts
|

THE POLLINATION REQUIREMENT OF THE FIELD BEAN (VICIA FABA)

Abstract: Many of the flowers on field bean plants fail to produce pods even when fully pollinated. When insect pollination is prevented pod production on the lowest inflorescences, which normally produce most pods, is reduced but a compensatory increase on the upper ones ensures a moderate yield. This change in the distribution of pods may be a useful indication of insufficient pollination.Areas in which crops requiring pollination are grown usually contain some pollinating insects, such as honey-bees kept by local bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
1

Year Published

1967
1967
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 3 publications
0
14
0
1
Order By: Relevance
“…The present investigation Field beans are intermediate in breeding be-was undertaken with the objective of throwing haviour between completely cross-pollinated and some light on the nature of this barrier and how completely self-pollinated crops (Fyfe & Bailey, hybrids and self-pollinating lines overcome it. Such 1951) and their seed set is markedly reduced in the knowledge is of interest both intrinsically and as an absence of pollinating bees (Riedel & Wort, 1960; aid in the development of self-pollinated varieties Scriven, Cooper & Allen, 1961;Free, 1966). Devel-of field beans, opment of completely self-pollinated varieties is being sought (Lawes, 1973) to eliminate dependence MATERIALS AND METHODS on bees for pollination, thereby avoiding fluctuations in yield caused by variations in the availa-The material studied (Table 1) comprised inbred bility and activity of bees.…”
Section: Discussionmentioning
confidence: 99%
“…The present investigation Field beans are intermediate in breeding be-was undertaken with the objective of throwing haviour between completely cross-pollinated and some light on the nature of this barrier and how completely self-pollinated crops (Fyfe & Bailey, hybrids and self-pollinating lines overcome it. Such 1951) and their seed set is markedly reduced in the knowledge is of interest both intrinsically and as an absence of pollinating bees (Riedel & Wort, 1960; aid in the development of self-pollinated varieties Scriven, Cooper & Allen, 1961;Free, 1966). Devel-of field beans, opment of completely self-pollinated varieties is being sought (Lawes, 1973) to eliminate dependence MATERIALS AND METHODS on bees for pollination, thereby avoiding fluctuations in yield caused by variations in the availa-The material studied (Table 1) comprised inbred bility and activity of bees.…”
Section: Discussionmentioning
confidence: 99%
“…An increased fertilization frequency at the upper flowering nodes of the AS plants was also observed (data not shown). The change in the distribution of pods was considered to be a useful indication of insufficient pollination (Reidel and Wort 1960). Setting pods at the upper flowering nodes was considered to be a good reproductive strategy that compensates the insufficient pollination, which ensures that some seeds are produced on a plant (Rowland et al 1983).…”
Section: Pollination and Fertilization Among Hybrids And Segregantsmentioning
confidence: 99%
“…Even in less severe conditions only about 24% of the ovules develop into mature seeds (Rowlands, 1960). Riedel & Wort (1960) concluded that pollination was not a factor limiting production and the observation that removing the apex of the plant at the right stage can increase the proportion of flowers developing pods also suggests that more flowers are fertilized than pods are set (Chapman, Guest & Peat, 1978). Furthermore, flower abortion has been considered a post-fertilization phenomenon caused by embryo abortion (Rowlands, 1960;Chapman, Fagg & Peat, 1979), usually after the 8-to 12-day stage of embryo development (Rowlands, 1964).…”
Section: Introductionmentioning
confidence: 99%